Generating the open space 3D model based on LiDAR data - Kalantaitė, Aušra; Paršeliūnas, Eimuntas Kazimieras; Romanovas, Denis; Šlikas, Dominykas (Geodesy and Cartography, 2012)
An open space could be defined as a space, which is restricted by a surface, that is generated over the physical Earth‘s surface, natural and artificial objects, and in which the distances between its objects are less than given critical tolerance. In other words, we have in mind the moving objects of certain dimensions, which could freely move in such an open space. The technological peculiarities of an open space 3D model generation are analysed. In general, the two sources of data were suggested to apply: the raw LiDAR data and the orthophotomaps. The method for generating an open space surface is presented too. An open space 3D model of the experimental territory was generated. The data of single orthophotomap on a scale of 1:10000 was applied. LiDAR and orthophotomap data is for the year 2009.